Beneficios de las soluciones nutritivas, para el desarrollo y crecimiento de plantas hidropónicas del cultivo de lechuga (Lactuca sativa L.)” - Aguilar Ledesma, Luis Jordan (2022)
The present case work studies the benefits of nutritional solutions for the development and growth of hydroponic plants for growing lettuce (Lactuca sativa L.) Lettuce is a vegetable that has achieved great importance due to the great diversity of climates. and the adaptability it presents; It is consumed fresh or industrialized, since most horticultural crops are rich in vitamins and easily digestible. Conclusions ; lettuce is a vegetable that has achieved great importance due to the great diversity of climates and its adaptability; it is consumed fresh or industrialized; one of his problems in the cultivation of lettuce in hydroponics is that he has little knowledge about its management and, in turn, about the use of its nutritive solutions; The problems that arise are generally the factors that must be taken into account when growing in hydroponics, since if we use any hydroponic system, in which most of the problems arise from the lack of or too much water, humidity, temperature, or pH issues, plants that are overwatered will begin to experience root rot, this can often cause plants to stop forming new leaves. Any new leaves that do form will often be much darker than the others and the edges will turn brown. Excessive irrigation can also cause the formation of unwanted organic material, such as fungi, and these will cause the nutrient solutions to be unable to be used by the plants and will not have a good production or yield of the maximum and benefits of the crops. with the use of nutrients. The application of nutritive solutions in hydroponic vegetable crops to obtain a greater and better-quality production using the benefits of the nutritive solutions will have to give a better management of the NS and in turn a greater control of the crop and to achieve this, programs and good management and use of fertilizers, recipes and complete fertilizers.